"How" is more important than "how much" for game possession in elite northern hemisphere rugby union - Alexandru Nicolae Ungureanu; Paolo Ricardo Brustio; Luca Mattina; Corrado Lupo (Termedia Publishing House, 2019)
The present study aimed to analyse technical and tactical aspects of rugby teams competing in the 2016/17 PRO12 Championship (12 professional club teams from Wales, Scotland, Italy, and Ireland) according to: margin of victory (close and balanced games, 1-9 and 10-26 points of difference in final score, respectively), ranking position [the four best placed clubs from each nation (the 1st-4th team) and the three following ranked clubs (the 5th-7th team)], and game outcome and ranking combined (winning and losing performances in the 1st-4th and 5th-7th team subgroups). One hundred and thirty-two games were analyzed according to 20 key performance indicators. A non-parametric approach was applied to evaluate differences (p≤0.05) between teams. In close games, winning teams reported less possession (p=0.039), defended more (tackles made, p=0.039), and carried the ball less than losing counterparts (p=0.05), whereas in balanced games, winning teams were found to be much better than losers in "tries for" (p<0.0001) as well as "tries against" (p<0.0001), and "clear breaks" (p=0.0003). The teams of the 1st-4th subgroups were found to be more oriented to provide a solid defence than the 5th-7th winning teams, which were more offensive oriented (possession, p=0.01; gain line carries, p=0.001; passes, p<0.0001). Finally, a similar scenario to that of balanced games emerged for winning and losing performances in the 1st-4th and 5th-7th team subgroups. Coaches and physical trainers of elite northern hemisphere rugby union teams should be aware that successful performances mainly consist of a strong defence, tackling, scrumming, breaking the defensive line and high occurrences of possessions during the attacking phase.